Gravity Surveying in Great Britain (cd8a87b4-f337-4723-a5a3-eb496ec900e9) - H. Shaw (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
IT is now generally recognized that the gravitational method of geophysical surveying is a valuable aid in elucidating the geological structure of the subsoil and enables the practical geologist to deduce the presence of useful deposits. The particular suitability of the torsion balance to the location of large and important subterranean structures has given rise to a wide application of this method by many of the important oil companies in their search for future supplies, and so intense have been these efforts that little has been heard of the method in other connections, with the exception of occasional references to its application in the location of hidden deposits of metallic ores, salt and lignite, and a number of accounts of its use in the elucidation of geological structures. Its success in the location of salt domes is well known, and establishes it as one of the most important of the geophysical methods, especially for the indirect location of oil. In the British Isles, however, no large occurrence of oil is likely to be revealed, and here the practical application of the gravitational method has been restricted almost entirely to the search for ores. This type of survey possesses well marked characteristics, and presents a gravitational problem that has necessitated the development of a special and probably unusual plan of campaign, full details of which it is hoped will shortly be published. The problems and difficulties encountered in this work are of necessity fundamentally related to those met with in the search for oil by means of the torsion balance, but they also possess several special and distinctive features which undoubtedly differentiate them from the obstacles confronting the oil prospector, and which call for special consideration and treatment.